Effect of conventional retting of jute on the quality of water and jute fiber - Ali, MR; Kabir, M; Shawon, MTS; Hussain, MM; Islam, MH; Alam, M (Progressive Agriculture, 2022)
Jute is a natural fiber also known as golden fiber in Bangladesh. Jute fiber is commonly extracted from the plant after immersion in water bodies. The traditional jute retting process harms the quality of jute fiber as well as water where jute plants were immersed as it decomposes bio-mass and hampers different water quality indicating parameters. In this study water samples were collected from different ponds and ditches at Muktagacha Upazilla, Mymensingh, Bangladesh in July 2020. Samples were collected from jute pre- and post-retting water bodies. The study was conducted to monitor the effect of jute retting on various physicochemical and microbiological parameters like- pH, total dissolved solids (TDS), electrical conductivity (EC), and dissolved oxygen (DO). All parameters were measured at the central laboratory of Bangladesh Agricultural University using a Multiparameter waterproof meter with a probe. To examine water quality, water samples were collected three times from five particular water bodies of stagnant waters, and the freshwater of the canal and pond. Water quality parameters of pre and post-retting jute water were found as pH 6.42~7.02 and 6.10~5.59, TDS 18~81 mgL-1and 103~183 mgL-1, DO 2.3~2.4 mgL-1and 0.8~0.9 mgL-1, and EC 36~163 µScm-1and 222~396 µScm-1, respectively. A comparison was made with the standard values of water quality parameters and found notable differences with the Department of Environment standards of Bangladesh. Another observation was also made to determine whether the retting water can influence fiber quality or not. Observed results indicated that a low level of pH and DO in jute retted water in a pond may not be suitable for fish cultivation. On the other hand, higher content of TDS and EC in post jute retting water was found responsible for the poor quality of jute fiber. Progressive Agriculture 32 (2): 151-161, 2021